4. EVALUASI KINERJA PEMERINTAHAN SBY-JK (Dari sujud pandang ekonomi dan kesejahteraan) - Ngatno, Ngatno (FORUM, 2007)
SBY-JK Govermnet has been worked out for 2.5Â  years to present. Evaluation result from the economic point of view reveals that the wealth is not satisfying. The Government performance has been good in macros level, being proved with 5.6% economic growth, and inflation rate is less than 10% . But, at the micros level, this one is unsatisfying, that poverty rate is high, 39.5 millions, and the unemployment is 10.22 millions.